Balancing Innovation and Ethics: Empirical Insights into AI Predictive Marketing Challenges and Opportunities - Latif, Nashrudin; Bungin, Burhan; Kodrat, David Sukardi (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This research endeavors to explore the ethical ramifications when artificial intelligence is utilized in predictive marketing, especially regarding potential pitfalls like algorithmic bias, infringements on privacy, the deliberate manipulation of consumer actions, and the aggregation of market power, which may undermine fair business competition.Methodology: A qualitative methodology was adopted for this study, involving In-Depth Interviews (IDIs) with a total of eight informants. The participants, who were data analysts and digital marketers representing various industry sectors, were recruited using both purposive and snowball sampling techniques. Data gathering spanned a six-week period and was subjected to thematic analysis to identify the prominent themes and issues.Finding: Five main themes were found in this study: (1) the importance of fairness and non-discrimination in algorithms, (2) transparency in data governance, (3) protection of consumer privacy, (4) risk of behavioral manipulation, and (5) ethical implications of market share concentration by AI-based companies.Conclusion: While AI can improve marketing efficiency, its use also risks creating social injustice and lowering consumer trust. Therefore, continuous data audits, transparent algorithm development, and strong consumer protection regulations are needed to ensure fair, ethical, and sustainable application of AI.